Effectiveness Of Student-Centered Learning Approach In Physical Education At Candipari Elementary School, Porong, Sidoarjo - Chusnul Chabibah Ilhama; Satunggale Kurniawan (Jambura Arena Sport, 2026)
This study was motivated by the dominance of teacher-centered approaches in physical education, which often result in low student engagement and limited opportunities for active participation. The purpose of this research was to analyze the effectiveness of the Student-Centered Learning (SCL) approach in improving the quality of physical education learning at Candipari Elementary School, Porong, Sidoarjo. This study employed a qualitative descriptive design involving one physical education teacher and students who participated directly in the learning process. Data were collected through observations, interviews, and documentation. Data analysis followed the interactive model consisting of data reduction, data display, and conclusion drawing to ensure systematic interpretation of the findings. The results indicate that the implementation of SCL increased student participation, learning enthusiasm, motor skills, and social interaction during physical education activities. Improvements were also identified in affective aspects, including discipline, responsibility, and sportsmanship. Although several challenges were encountered, particularly limited facilities and varying levels of teacher readiness, the approach remained effective in creating a more active and meaningful learning environment. The novelty of this study lies in its theoretical contribution: it extends constructivist accounts of SCL by demonstrating that student agency and meaning-making can be sustained even when material resources are constrained, showing that teacher facilitation skill, rather than facility adequacy, is the primary condition enabling active knowledge construction. This context, an elementary school with limited educational resources and diverse student abilities, has received limited attention in previous physical education research. The findings suggest that SCL can serve as an innovative and adaptable strategy for enhancing the quality of physical education learning in resource-constrained elementary schools